Comparative analysis of chemical profiles and antioxidant activities of essential oils obtained from species of Lippia L. by chemometrics. (1st August 2022) - de Fatima Alves Nonato, Carla; Camilo, Cicera Janaine; Duarte Leite, Débora Odília; Lúcio Albuquerque da Nobrega, Mário Gustavo; Ribeiro-Filho, Jaime; Alencar de Menezes, Irwin Rose; Tavares, Josean Fechine; Martins da Costa, José Galberto
Graphical abstract: Highlights: The similarity and antioxidant activity of Lippia essential oils were investigated. Essential oils studied have no relationship between their chemical compositions. The compounds present in L. alba showed greater antioxidant effectiveness. L. sidoides essential oil had the lowest IC50 in different antioxidant mechanisms. Abstract: Due to the importance of diseases associated with oxidative stress, the search for natural antioxidants proves to be essential. This work aimed to compare the chemical composition and antioxidant potential of essential oils from the genus Lippia L. through chemometric analysis. The essential oils were characterized by gas chromatography coupled with mass spectrometry. Antioxidant potentials were determined by DPPH, ABTS, Deoxyribose and β -carotene protection, Iron chelation and reduction methods. All data were related by multivariate analyzes. Essential oils showed low similar chemical compositions and no statistically significant relationship. These showed relevant antioxidant activity, especially for L. sidoides that obtained IC50 of 5.22 ± 0.08 µg/mL in ABTS capture. Multivariate analyzes showed the effectiveness of L. alba compounds to DPPH scavenging, Fe 3+ reduction and β -carotene protection, and L. gracilis components to deoxyribose protect. Thus, studies proving the antioxidant potential of Lippia compounds against oxidative stress and their use in food conservation are fundamental.